Adição de ácido clorogênico ao diluente de sêmen suíno com maior sensibilidade ao resfriamento: avaliação dos parâmetros espermáticos - Rech, Rodrigo Dalmina (2020)
The objective of this study was to evaluate the viability of Inseminating Doses (DI) of pigs with ejaculates classified as sensitive to packaging at 17 ℃, plus chlorogenic acid and to identify which concentration of the antioxidant obtained the best efficiency in maintaining the fertilizing capacity over 168 hours. Stage I included 25 pigs, collected once a week, for 5 consecutive weeks, totaling 5 ejaculates per animal. The produced DIs were analyzed for Progressive sperm motility (MP) at hours 0, 120 and 168 and classified in groups, according to the sensitivity to cooling, being higher, medium and lower sensitivity, tabulating and classifying the data in a spreadsheet of the as follows: MP <60% in 120 hours (higher); MP ≥ 60% in 120 hours and <60% in 168 hours (average) and MP ≥ 60% in 168 hours (lowest). Four breeders were obtained that had at least three of the five ejaculated in the first selection pattern. In Stage II, these pre-selected animals were collected for 4 weeks, once a week, totaling 4 ejaculates per animal, with the 45 ml DIs submitted to five treatments: T1: DI with Androstar® Plus (AND) (control) ; T2: DI with AND + chlorogenic acid (ChA - Chlorogenic acid crystalline, C3878 - Sigma-Aldrich ®) (1,500 μg DI-1); T3: DI with AND + ChA (3,000 μg DI-1); T4: DI with AND + ChA (4,500 μg DI-1); T5: DI with AND + ChA (6,000 μg DI-1). The sperm parameters were evaluated by CASA, Flow Cytometry, Term Resistance Test (TTR) and Sperm Morphology up to 168 hours of the study. TM at T1 was 4.43% higher (p <0.05) compared to T4. In MI, T4 was 17.21% higher (p <0.05) than T1. As for the hours, MT and MP decreased (p <0.05) from 18.52% and 22.84%, respectively, during the period from H0 to H168. In ML and IM there was an increase (p <0.05) of 22.95% and 64.19%, respectively, from H0 to H168. At TTR, TM at T1 was 7.86% higher (p <0.05) than T4. The variable IM presented T4 17.98% higher (p <0.05) than T1. In the hours of TTR assessment, MT decreased (p <0.05) 3.87% from H120 to H168 and IM increased (p <0.05) 8.89% for the same period. In sperm morphology, the primary changes (PR) in H0 were 68.97% higher (p <0.05) compared to H120 and 31.16% higher (p <0.05) compared to H168. The IN variable was 20.45% higher (p <0.05) in H120 compared to H0 and 11.91% higher (p <0.05) in relation to H168. In the membrane integrity, the ARML and AIMI values were 63.27% higher in H0 (p <0.05) than H168 and in H168 3.57% higher (p <0.05) than H0, respectively. The addition of chlorogenic acid, in the concentrations used, has no benefits in prolonging sperm viability. Still, there was no improvement in sperm morphology and membrane integrity after 168 hours of storage at 17 degrees Celsius